2015
DOI: 10.1108/mrr-02-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Social sustainability in the supply chain: analysis of enablers

Abstract: Purpose – This study aims to identify various enablers and the inter-relationships among them in adopting social sustainability measures in the supply chain. Social sustainability in the supply chain has received growing attention in the recent years, due to growing awareness on equity, health and safety, education, child and bonded labor and ethical practices in corporates. Design/methodology/approach – Various enablers and their contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 110 publications
5
53
0
1
Order By: Relevance
“…There are only initial efforts (e.g., Mani et al. ; Spence and Rinaldi ; Varsei et al. ) that reveal how internal and external factors, such as firm capabilities or supply‐chain structure, hinder or enable SLCA practices to respond to stakeholders’ expectations.…”
Section: Critical Shortcomings and Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only initial efforts (e.g., Mani et al. ; Spence and Rinaldi ; Varsei et al. ) that reveal how internal and external factors, such as firm capabilities or supply‐chain structure, hinder or enable SLCA practices to respond to stakeholders’ expectations.…”
Section: Critical Shortcomings and Research Implicationsmentioning
confidence: 99%
“…First, more research is needed to investigate factors that determine the implementation, success, and failure of SLCA in business practice. There are only initial efforts (e.g., Mani et al 2015;Spence and Rinaldi 2014;Varsei et al 2014) that reveal how internal and external factors, such as firm capabilities or supply-chain structure, hinder or enable SLCA practices to respond to stakeholders' expectations. Furthermore, there is only a limited understanding of how companies perceive the relevance of social performance issues and what indicators they perceive as particularly useful in decision making (e.g., Harms et al 2013).…”
Section: Critical Shortcomings and Research Implicationsmentioning
confidence: 99%
“…Jayalakshmi and Pramod (2015) adopted ISM method to identify and analyse the flexible control systems for industry. Similarly, Mani et al (2015d) determined various social sustainability enablers in manufacturing industries using ISM method. Mathiyazhagan et al (2013) have used ISM method to identify and model the barriers associated to green sustainability adoption in Indian manufacturing Industries.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, significant result of this study consistent with other studies in this area where direct linking of small farmers to market, traders , exporters, manufacturer raises income of farmers, secure market at agreed price, and ensure trust (Praveen, K.V, 2014). Besides this, previous studies have focused on inter relationship or interdependency between farmers and suppliers and other actors, agro food supply chain management, market place for agriculture products, and contract farming along with private sector initiatives, rather than just focusing over independent farmer market (Ascione, Cristiano, & Tarangioli, 2011;Kumar, Agrawal, & Sharma, 2013;Mani, Agrawal, & Sharma, 2015;Somashekhar, Raju, & Patil, 2014). With regard to agro food supply chain context, this study has found relative advantage, and has PhD Thesis Keshav Prakash Dandage Discussions 100 | P a g e highlighted the need for smallholder farmers to be aware of the relative advantage of direct trading gateway instead of stepwise process.…”
Section: Implementation Of Food Traceability System In Indiamentioning
confidence: 99%